Contribution of Power Dynamics and Women ’ s Perceptions to Girls ’ Education among Pastoral Communities in Tanzania - Mtey, Adella Raymond (Papers in Education and Development, 2021)
This paper explored power relations, women ' s perceptions and their contribution to girls ' formal education among pastoral communities in Tanzania. Post-colonial feminist theory underpinned the theoretical discussion of the findings. The study adopted qualitative research approach and a case study design. Purposive and opportunistic sampling techniques were used to select twenty women who participated in the study. Data was collected using in-depth interviews and field observations and then analysed thematically. The findings indicate women ' s positive perceptions towards girls ' education. Findings also revealed persistent unequal power relations, which hinder equal decision making about girls ' participation in education. The study recommends policy maker to consider women ' s voices in developing education programmes which cater for women ' s well-being. Keywords: formal education, maasai, pastoralists, perceptions, power relations